2022
DOI: 10.3390/plants11040568
|View full text |Cite
|
Sign up to set email alerts
|

Effective Utilization of Vaccinium virgatum Aiton Stems as Functional Materials: Major Constituent Analysis and Bioactivity Evaluation

Abstract: We previously reported that rabbit-eye blueberry (Vaccinium virgatum Aiton) leaves exhibit multiple functions. In this study, we evaluated whether V. virgatum stems can also be used as functional materials similar to leaves and clarified the major constituents and their biological activity (antioxidant activity and anti–adult T cell leukemia (ATL) activity). Water extracts of V. virgatum stems were separated into 19 fractions using a Diaion HP-20 open column. Sugars and organic acids were detected in the highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The structure of PAC was then identified by liquid chromatography/mass-ion trap-time of flight analysis and butanol-HCl hydrolysis analysis. On the other hand, it was confirmed that PAC was present on the V. virgatum stem by the 4-dimethylaminocinnamaldehyde (DMACA) method in our previous report [ 18 ].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…The structure of PAC was then identified by liquid chromatography/mass-ion trap-time of flight analysis and butanol-HCl hydrolysis analysis. On the other hand, it was confirmed that PAC was present on the V. virgatum stem by the 4-dimethylaminocinnamaldehyde (DMACA) method in our previous report [ 18 ].…”
Section: Introductionmentioning
confidence: 63%
“…In our most recent study, we analyzed the fractions obtained from water extracts of V. virgatum stems for the ability to inhibit the proliferation of ATL cell lines [ 18 ]. However, questions regarding which organ contains the most active components, or which is stronger when mixed, have not been rigorously tested in individual plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations